2014
DOI: 10.5194/acpd-14-26257-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fossil vs. non-fossil sources of fine carbonaceous aerosols in four Chinese cities during the extreme winter haze episode in 2013

Abstract: The comment was uploaded in the form of a supplement: https://www.atmos-chem-phys-discuss.net/acp-2017-340/acp-2017-340-AC1-supplement.pdf Interactive comment on Atmos. Chem. Phys. Discuss., https://doi.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…These carbon particles in the atmosphere have two sources: fossil fuel (FF, e.g., from traffic exhaust, coal combustion, industry) and non-fossil (NF, e.g., from open/forest fire, biofuel burning, biogenic emission) emissions. Their unambiguous source apportionment has been conducted in recent years by the measurements of radiocarbon ( 14 C) (Gustafsson et al, 2009, Szidat et al, 2009Chen et al, 2013;Liu et al, 2013;Huang et al, 2014;Liu et al, 2014;Zotter et al, 2014a;Andersson et al, 2015;Zhang et al, 2015). This radioisotope (half-life ¼ 5730 years) enables a distinction between FF and NF sources because 14 C is absent in FF, but present at the current ambient level in NF materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These carbon particles in the atmosphere have two sources: fossil fuel (FF, e.g., from traffic exhaust, coal combustion, industry) and non-fossil (NF, e.g., from open/forest fire, biofuel burning, biogenic emission) emissions. Their unambiguous source apportionment has been conducted in recent years by the measurements of radiocarbon ( 14 C) (Gustafsson et al, 2009, Szidat et al, 2009Chen et al, 2013;Liu et al, 2013;Huang et al, 2014;Liu et al, 2014;Zotter et al, 2014a;Andersson et al, 2015;Zhang et al, 2015). This radioisotope (half-life ¼ 5730 years) enables a distinction between FF and NF sources because 14 C is absent in FF, but present at the current ambient level in NF materials.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2013) first systematically investigated the 14 C signals of EC (or black carbon) in Beijing, Shanghai, and Xiamen, and found that 83e86% of EC was associated with FF combustion during the 2009e2010 winter, with the remainder derived from biomass burning (BB). Zhang et al (2015) analyzed the 14 C levels of OC and EC in four Chinese citieseBeijing, Xi'an, Guangzhou, and Shanghaieand found that the contributions of FF sources to OC and EC were 35e49% and 57e80%, respectively, in January 2013. Andersson et al (2015) found that during this haze period FF sources on average contributed 74%, 68% and 68% to EC in Beijing, Shanghai and Guangzhou, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the synoptic condition, winds at the surface layer were very weak with the wind speed lower than 2.0 m s relative humidity was usually 100%. The high-pressure, weak winds and high relative humidity were unfavorable for the dispersion of pollutants (Gao et al, 2015;Zhang et al, 2015a) which caused the accumulation of pollutants in Beijing. Furthermore, the previous source regions totally shifted from northwesterly to southerly.…”
Section: Air-flow Trajectoriesmentioning
confidence: 99%
“…Thus, the OC/EC ratios in the urban air (4.10 ± 2.26) were significantly lower than those in the rural air (5.82 ± 2.51) (p b0.001). This was probably due to more PM associated with fossil emissions from coal combustion and vehicle exhaust in the urban area than in the e-waste area, which are thought to be the primary sources of EC (Liu et al, 2014;Zhang et al, 2015) and/or different emission sources of PM at the two sites. In addition, at both urban and rural sites, the OC/EC ratios in dry seasons (winter and fall) (4.30 ± 1.49 and 7.33 ± 2.46, respectively) were significantly higher than those in wet seasons (summer and spring) (3.02 ± 2.28 and 5.18 ± 1.72, respectively).…”
Section: Characteristics Of Pmmentioning
confidence: 99%